Understanding Users' Decisions to Adopt Canva: The Roles of Perceived Ease of Use, Perceived Behavioral Control, and Word of Mouth - Athalia Farah Anggita Sriwidari; Restu Frida Utami; Suyoto; Dian Widyaningtyas (Al-Qalam Institue, 2026)
This study aims to examine the influence of Perceived Ease of Use, Perceived Behavioral Control, and Word of Mouth on the decision to use the Canva application. This research employed a quantitative approach using a survey method. Data were collected from 133 Canva users selected through purposive sampling and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 3. The findings indicate that Perceived Ease of Use, Perceived Behavioral Control, and Word of Mouth each have a positive and significant effect on the decision to use the Canva application. Among these variables, Word of Mouth demonstrates the strongest influence, indicating that user recommendations play a crucial role in encouraging application usage decisions. These findings imply that Canva should prioritize enhancing user experience by improving ease of use and strengthening users’ confidence in using the application while encouraging positive user recommendations to increase adoption and usage decisions. The study also contributes to the understanding of technology adoption by highlighting the importance of behavioral and social factors in influencing users’ decisions.